Pendampingan Remaka Dengan Youth Learning Community Model Di Paroki Santo Gabriel Pulang Pisau - Stefanus Stefanus; Fransiskus Janu Hamu; Agnes Angi Dian Winei (Sepakat : Jurnal Pastoral Kateketik, 2023)
This study aims to offer a model of mentoring the youth learning community in the Santo Gabriel Pulang Pisau Parish. The model is called the Youth Learning Community in assisting youth at Santo Gabriel Pulang Pisau Parish, as a means of cultivating the development of youth faith. This study also describes previous assistance used for mentoring youth at the Santo Gabriel Pulang Pisau Parish. This research uses a qualitative approach with descriptive methods. The research data was obtained using interviews conducted with 4 youths, 1 Senior OMK, 1 Catechist and 1 Priest. The data obtained was analyzed with the benefit of the "Miles" analysis method which was divided into three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of the research, it was concluded that the mentoring program through the pastoral program had not been implemented optimally. This conclusion was based on the statement of one informant who revealed that "the assistance has been running so far, but programmatically through the parish program has not run optimally. Therefore, this research offers a model for youth accompaniment as a pastoral strategy to foster youth faith development.